Secretion of transthyretin: molecular mechanisms dependent on the endoplasmic reticulum - Meng, Jia; Cai, Shan-jun (Frontiers in Physiology, 2025)
Hereditary transthyretin amyloidosis (ATTRv) results from genetic mutations that destabilize transthyretin (TTR), leading to the formation of extracellular aggregates and amyloid fibrils. A common pathological feature of ATTRv is the capacity of TTR variants to evade endoplasmic reticulum quality control (ERQC) and be secreted, underscoring the critical role of ER regulation in disease pathogenesis. Notably, the TTR Gly83Arg mutation causes familial vitreous amyloidosis, a subtype distinguished by abnormal TTR deposition in the ocular vitreous cavity. Current therapies for ATTRv are ineffective in crossing the blood-retinal barrier or in halting the progression of ocular amyloidosis. This review summarizes the molecular mechanisms of ER-regulated TTR secretion and explores potential causes of ocular amyloid deposition, aiming to provide mechanistic insights into familial vitreous amyloidosis.